The Influence of Service Quality, Facilities and Location on The Decision to Stay at The Bountie Hotel and Convention Center Sukabumi - Ishak, Riani Prihatini; Mayasari, Dina; Skawanti, Julia Ratnawulan; Andani, Rian (Institut Pariwisata Trisakti, 2024)
Purpose of this study is to assess the influences among service quality, facility and location to stay decision use service inn on The Bountie Hotel and Convention Center Sukabumi. This is a quantitative-descriptive research using multiple linear regression test. The sampling technique used the probability sampling, simple random sampling, and sampled customers who stayed and was calculated using Slovin formula. As for sample which in set in research this is 100 consumers had stayed at this hotel. Collection data method used on this study by questionnaire corresponding with criteria study. The result of this study shows that (1) service quality variable has a positive and significant effect on the decision to stay, (2) facilities s have a positive and significant effect on the decision to stay, (3) location has a positive and significant effect on the decision to stay and (4) service quality, facilities and location altogether have positive and significant effect on the decision to stay at The Bountie Hotel and Convention Center Sukabumi. Keywords: service quality, facility, location, stay decision